Microplastics in the Mediterranean: Variability From Observations and Model Analysis - Tsiaras, Kostas; Costa, Elisa; Morgana, Silvia; Gambardella, Chiara; Piazza, Veronica; Faimali, Marco; Minetti, Roberta; Zeri, Christina; Thyssen, Melilotus; Ben Ismail, Sana; Hatzonikolakis, Yannis; Kalaroni, Sofia; et al. (Frontiers in Marine Science, 2022)
In this study, the abundance and properties (size, shape, polymer type) of microplastics (MPs) in sea surface water samples, collected during two sampling campaigns over 2018-2019, in four coastal areas of the Mediterranean Sea (Saronikos Gulf, LIgurian Sea, Gulf of Lion, Gabes Gulf) were investigated. Coupled hydrodynamic / particle drift model simulations with basin-scale Mediterranean and high resolution nested models were used to provide a better understanding on the variability of the abundance/size of MPs, originating from wastewater and river runoff, in the four areas. Different size classes of MPs were considered in the model, taking into account biofouling induced sinking, as a possible mechanism of MPs removal from the surface. The Gabes Gulf showed the highest mean MP abundance (0.073-0.310 items/m2), followed by Ligurian Sea (0.061-0.134 items/m2), Saronikos Gulf (0.047-0.080 items/m2) and Gulf of Lion (0.029-0.032 items/m2). Overall, the observed MPs abundance and size distribution was reasonably well reproduced by the model in the four different areas, except an overestimation of small size contribution in Saronikos Gulf. The basin-scale simulation revealed a strong decrease of smaller size MPs in offshore areas, due to biofouling induced sinking, with larger (floating) MPs being able to travel longer distances in the open sea. A significant impact of waves drift and advection of MPs from non-local sources was identified from model simulations, particularly in the Gulfs of Lion and Gabes, having a stronger effect on larger microplastics. In Gabes Gulf, most MPs originated from offshore areas, being mainly (floating) larger size classes, as suggested by the observed quite small contribution of <1 mm particles. The MPs observed abundance distribution in each area could be partly explained by the adopted sources distribution. The modeling tools proposed in this study provide useful insight to gain a better understanding on MPs dynamics in the marine environment and assess the current status of plastic pollution on basin and regional scale to further develop environmental management action for the mitigation of plastic pollution in the Mediterranean Sea.